The use of alternative polyadenylation sites renders β1- integrin mRNA isoforms with differential stability during mammary gland development - Naipauer, Julian (2013)
Integrins are heterodimeric cell-surface adhesion receptors that play a critical role in tissue development. Characterization of the full-length mRNA encoding the β1 subunit (Itgb1) revealed an alternative functional cleavage and polyadenylation site that yields a new Itgb1 mRNA isoform 578 bp shorter than that previously reported. Using a variety of experimental and bioinformatic approaches, we found that the two Itgb1 isoforms are expressed at different levels in a variety of mouse tissues, including the mammary gland, where they are differentially regulated at successive developmental stages. The longer mRNA species is prevelant during lactation, whereas the shorter is induced after weaning. In 3D cultures, where expression of integrin β1 protein is required for normal formation of acini, experimental blockade of the longer isoform induced enhanced expression of the shorter species which allowed normal morphological mammary differentiation. The short isoform lacks AU-rich motifs and miRNA target sequences that are potentially implicated in the regulation of mRNA stability and translation efficiency. We further determined that the AU-binding protein HuR appears to selectively stabilize the longer isoform in the mammary gland. In summary, the results of the present study identify a new regulatory instance involved in the fine-tuning of Itgb1 expression during mammary gland development and function.